The Role of I. V. Stalin in the History of Architecture - Rappaport, Alexander (project baikal, 2016)
The critique of “constructivism” and implementation of “stalinist empire” style in the USSR is regarded as a general trend in the course of revolutionary shift to modern mass society in the West culture, producing “kitch” as a hybrid of aristocratic and popular taste in urban environment. This turbulent process produces a total relativity of moral and artistic values, tastes and the concepts of style. The idea of truth and beauty becomes conventional. The future of postmodernist kitch is still obscure.
Keywords: kitch; taste; relativity; opinion; style; totalitarism; mass society